2017
DOI: 10.1155/2017/8293207
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum ANGPTL8 Concentrations in Patients with Prediabetes and Type 2 Diabetes

Abstract: The objectives of the study were to investigate serum ANGPTL8 concentrations in different glucose metabolic statuses and to explore the correlations between serum ANGPTL8 levels and various metabolic parameters. Serum ANGPTL8 levels were determined using ELISA in 22 subjects with NGT (normal glucose tolerance), 74 subjects with IGR (impaired glucose regulation), and 33 subjects with T2DM (type 2 diabetes mellitus). Subjects with IFG, IGT, CGI, and T2DM had higher levels of serum ANGPTL8 than subjects with NGT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…On the other hand, ANGPTL8 has been linked to insulin resistance and lipoprotein metabolism, two functionally important processes in the development of type 2 diabetes and CVD [ 47 ]. In recent studies, association of ANGPTL8 with diabetes and atherosclerotic diseases has gained much interest.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ANGPTL8 has been linked to insulin resistance and lipoprotein metabolism, two functionally important processes in the development of type 2 diabetes and CVD [ 47 ]. In recent studies, association of ANGPTL8 with diabetes and atherosclerotic diseases has gained much interest.…”
Section: Discussionmentioning
confidence: 99%
“…ANGPTL8/betatrophin (also known as HCC associated protein, TD26, or lipasin) [54,55] is expressed primarily in liver and visceral adipose tissue (VAT), and is associated with liver steatosis and increased plasma triglyceride levels in humans [55,56]. Serum levels of ANGPTL8 are significantly increased in IR [57] and T2DM [58,59]. ANGPTL8 requires ANGPTL3 to act on LPL, while ANGPTL8 alone has no demonstrable effect on LPL [60].…”
Section: Hepatokinesmentioning
confidence: 99%
“…ANGPTL8 is mainly expressed in the liver, white and brown adipose tissue (5,6). Nutritional states, thyroid hormone, insulin receptor antagonists, sterol regulatory element-binding protein (SREBP) isoforms: SREBP-1a, SREBP-1c, LXR agonists, carbohydrate-responsive element-binding protein (ChREBP), 5 adenosine monophosphate-activated protein kinase (AMPK), and mitogen-activated protein kinase (MAPK) have major roles in the regulation of ANGPTL-8 expression (7).…”
Section: Introductionmentioning
confidence: 99%
“…This is a physiological response to increase beta-cell proliferation in order to counteract high insulin demand (39). Therefore, ANGPTL-8 may play a role before developing into diabetes mellitus (5,7). Some recent studies showed that ANGPTL-8 might be a predictive factor for diabetic complications, especially nephropathy and retinopathy (40).…”
Section: Introductionmentioning
confidence: 99%